An Analysis of English Speaking Materials in the Textbook “Bahasa Inggris SMA” based on Dat Bao’s Theory at the Eleventh Grade of SMA Swasta Santu Xaverius Gunungsitoli 2022/2023 - Gea, Nelman Tonius; Zebua, Elwin Piarawan; Harefa, Afore Tahir; Telaumbanua, Yasminar Amaerita (LP. Ma'arif Janggan Magetan, 2023)
This research aimed to analyze whether the content of “Bahasa Inggris SMA” textbook in the part of its speaking material is in line with Dat Bao’s theory. This research used descriptive research type with the content analysis. The data was English textbook “Bahasa Inggris SMA” used by eleventh grade students of SMA Swasta Santu Xaverius Gunungsitoli that consist of eight Chapters. The research instruments were textbook evaluation sheet and interview sheet. The data was then analyzed by using assessment rubric of Dat Bao’s theory that consists of four main aspects, namely; linguistic support, content-based and affective support, skill support, and diversity and flexibility. Thereafter, the researcher presented the data with percentage of scoring and interpreted it into a description paragraph. The result of study showed that English textbook “Bahasa Inggris SMA” did not successfully fulfill Dat Bao’s theory, where the linguistic support was (73.95%), content-based and affective support (48.43%), skill support (70.31%), and diversity and flexibility (58.31%). The percentage showed that it was still lacking of linguistic input in pronunciation section, lacking of supporting students’ cultural and visuals that support verbal learning, lacking of supporting communicative functions and strategies, and lacking of variety of speaking activities. From the research findings, the researcher suggested that the textbook needs to be developed in terms of its content of speaking materials. Subsequently, both ELT teacher and textbook writer should concern and pay attention with the content of the textbook suggested by Dat Bao’s theory.